2014
DOI: 10.1016/j.jphotochem.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The antagonistic and synergistic effects of temperature during solar disinfection of synthetic secondary effluent

Abstract: a b s t r a c tA 4-factor, multilevel, full factorial design of 240 experiments was performed in order to investigate the effect of temperature on the inactivation efficiency of spiked Escherichia coli in simulated solar disinfection of a synthetic secondary effluent. The initial population of the microorganisms was 10 3 , 10 4 , 10 5 and 10 6 CFU/mL, the exposure time 1, 2, 3 and 4 h, the treatment temperature 20, 30, 40, 50 and 60• C and the sunlight intensity 0, 800 and 1200 W/m 2 . Radical changes in bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 49 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…Marugan et al [43] have underlined the importance on Mg and K salts for the maintenance of bacterial life and Caballero et al [44] highlighted the aid nutrients provide in the growth of bacteria in water matrices. Therefore, optimal support conditions for bacterial development is expected, as seen in previous works with the same wastewater matrix [40,61]. Generally, increasing the dose decreases bacterial survival.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Marugan et al [43] have underlined the importance on Mg and K salts for the maintenance of bacterial life and Caballero et al [44] highlighted the aid nutrients provide in the growth of bacteria in water matrices. Therefore, optimal support conditions for bacterial development is expected, as seen in previous works with the same wastewater matrix [40,61]. Generally, increasing the dose decreases bacterial survival.…”
Section: Resultsmentioning
confidence: 82%
“…The chemicals were used as received. A 10% dilution of the said wastewater was inoculated with E. coli, to form a suspension containing 10 6 CFU/mL and bear organic carbon values closer to the desired ones [61].…”
Section: Methodsmentioning
confidence: 99%
“…An extensive analysis of the disinfection kinetics and the regrowth potential of the photo-treated secondary effluent was published before by the authors (Giannakis et al, 2014a;2014b). In summary, reverse results were observed for the process efficiency, when the DOE was analyzed;…”
Section: Challenging Reciprocity Law In Temperature-controlled Disinfmentioning
confidence: 95%
“…An hourly-drawn sample was kept in sterile plastic flasks in the dark, at room temperature (~25˚C), for post-irradiation measurements of survival/regrowth after 24 and 48 h. Experiments were performed twice, while sampling (and afterwards, plating) was done in duplicates, from 2-3 consequent dilutions. (Giannakis et al 2014a). Finally, the runs with null intensity were not used in dose calculations, as they reflect no dose impact and act as blank thermal treatment experiments.…”
Section: Experimental Details: Light Source Bacterial Enumeration Anmentioning
confidence: 99%
“…On the one hand, this behavior (Fig. 5a) is attributed to the reduced kinetics of the photo-Fenton reaction: it is known that temperature increases chemical reactions' kinetics, plus OrtegaGomez et al [61] revealed the reduced inactivation rate in another bacterial species but also mesophilic with similar optimal growth temperature with E. coli, according to the Arrhenius equation and on the other hand, treating wastewater at temperatures close to the optimal growth conditions, can delay bacterial inactivation [62].…”
Section: Environmental Influencementioning
confidence: 95%